A Novel Self-Compressing Single Screw for Subtalar Arthrodesis - Jason T. Bariteau MD; Liliana A. Ogden MD; Kasey Crockett (Foot & Ankle Orthopaedics)
Category: Hindfoot; Other Introduction/Purpose: Subtalar fusions have become the standard of care for a variety of pathologies of the hindfoot that have failed non-operative management, both as an isolated procedure or combined as a double or triple arthrodesis. Multiple fixation methods exist for this procedure, although newer technology has introduced the ability for sustained dynamic compression via the use of nitinol. The purpose of this work was to assess a new internal compressing screw on subtalar arthrodesis. Methods: We examined 15 patients who underwent subtalar fusion with a single screw utilizing an internal nitinol device. Serial radiographs were reviewed for migration of the nitinol implant over time, spanning from 3 months to up to a year post operatively. We also assessed for post-operative complications including nonunion, infection, and pulmonary embolism. Results: There was an average of 63% of recovered compression, ranging from 26%-88%. The majority of the recovery was within the first three months post operatively. Our follow up averaged 9.5 months (range, 3 months to 1 year 8 months). There was one patient with a nonunion of the subtalar joint and one patient who suffered a post-operative pulmonary embolus. There were no infections requiring surgical treatment. Conclusion: The nitinol element provides sustained compression to combat bone resorption or settling. While the majority of this is seen in the first three months, it is still possible to have more recovery beyond this time. This small case series demonstrates a low complication rate and high union rate with utilization of this implant. Future studies are needed to compare this fixation method to traditional screws and review differences in union rates and complications. Xrays taken at time of surgery, at 3 months post-op, and 1 year post-op of a 7×80mm screw with an available 3.0mm of post-operative compression. The implant had compressed nearly 50% at 3 months with additional compression noted between 3 months to 1 year post implantation.